Behavioral Finance in the Age of Technology: The Evolving Biases of Modern Investors - Svoboda, Andreas (International Journal of Social Science, Education, Communication and Economics, 2025)
The rapid integration of financial technology (FinTech), artificial intelligence (AI), and social media has transformed global investment behavior, reshaping the psychological dynamics of modern investors. This paper examines how digital technologies amplify behavioral biases such as overconfidence, herding, and recency bias within contemporary financial markets. Using a descriptive qualitative approach supported by literature synthesis and case studies, it explores the interplay between investor psychology and technological systems. Findings indicate that while FinTech platforms democratize access to financial markets, their gamified features and algorithmic personalization reinforce impulsive and emotionally driven trading. AI-based advisory systems, though designed to enhance decision accuracy, often introduce automation bias and confirmation loops that distort rational judgment. Social media ecosystems further accelerate herding and emotional contagion by promoting conformity through peer validation and viral sentiment. The study highlights ethical and regulatory challenges associated with behavioral exploitation and algorithmic transparency, emphasizing the need for robust investor protection frameworks and behavioral literacy programs. Ultimately, it concludes that technology in finance must balance innovation with responsibility, ensuring that digital tools empower investors without amplifying cognitive biases or undermining market integrity.